Mechanical Design and Prototype of Meatball Dough Grinder and Mixer Machine for Meat Processing in Indonesian Regions - Prabowoputra, Dandun Mahesa; Setiawan, Adi Febrianto; Ramadhana, Enrico Chandra; Onistia, Welsa Okta; Sulaiman, Robi; Arifiantio, Rokhmat; Prasetyo, Gagah Hari (Universitas Sebelas Maret, 2025)
A Meatball Dough Grinding-Mixing (MDGM) machine is a device that transforms raw meat into meatball dough through a combination of grinding and mixing processes, similar to a food processor or blender. The MDGM machine features four sharp stainless-steel blades. The rotation of the blade is driven by an electric motor with a power rating of 1 HP, operating at an engine speed of 2800 rpm. This engine speed is then transmitted through a belt pulley transmission with a diameter ratio of 3:5. The belt moves the installed blade at a rate of 1600 rpm. This MDGM machine has a capacity of 6 kg in one process. In this MDGM machine, one shaft stands vertically. The shaft has a diameter of 15 mm and a length of 400 mm. Pegs on the shaft, with dimensions of 6 mm in height and 6 mm in width, hold the rotating pulley in place when the engine is operating.